2023
DOI: 10.1021/acscatal.3c00415
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Metal–Support Interaction-Activated Sub-Nanometer Pt Clusters on FeOx Supports for Aqueous Phase Reforming and Hydrogenolysis of Glycerol

Abstract: The dynamic metal−support interaction (DMSI) plays a significant role in charge transfer, active site reconfiguration, and interface reconstruction between metals and oxide supports under redox conditions. However, developing an equilibrium between oxidation and reduction properties, greatly influenced by dynamic interactions, proves to be a considerable challenge when coupling a reforming reaction with a hydrogenation reaction. Herein, we engineered the DMSI effect between sub-nanometer Pt clusters and FeO x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Recently, nanometer size metal catalysts have shown excellent activity in energy-related reactions because of the low average metal–metal coordination number compared with those of large nanoparticles. , Nevertheless, stabilizing metal clusters during electrocatalytic processes remains challenging due to the absence of a restraining force against aggregation . Interestingly, it has been widely demonstrated that encapsulating metal sites with different supports can significantly enhance catalytic performance through strong metal–support interaction (SMSI). Among support materials, FeO x possesses abundant surface active sites, accelerating the hydrolytic dissociation kinetics on surfaces and water molecule decomposition. , Meanwhile, the synergistic effect between clusters and metal oxides can regulate the energy band structure and Fermi level at the catalyst interface, which optimize the adsorption and desorption of intermediate substances in specific steps. , Also, the synergistic effect can enhance the catalyst stability by forming an alloy or composite structure during the precipitation reaction to increase the resistance against corrosion and poisoning. …”
mentioning
confidence: 99%
“…Recently, nanometer size metal catalysts have shown excellent activity in energy-related reactions because of the low average metal–metal coordination number compared with those of large nanoparticles. , Nevertheless, stabilizing metal clusters during electrocatalytic processes remains challenging due to the absence of a restraining force against aggregation . Interestingly, it has been widely demonstrated that encapsulating metal sites with different supports can significantly enhance catalytic performance through strong metal–support interaction (SMSI). Among support materials, FeO x possesses abundant surface active sites, accelerating the hydrolytic dissociation kinetics on surfaces and water molecule decomposition. , Meanwhile, the synergistic effect between clusters and metal oxides can regulate the energy band structure and Fermi level at the catalyst interface, which optimize the adsorption and desorption of intermediate substances in specific steps. , Also, the synergistic effect can enhance the catalyst stability by forming an alloy or composite structure during the precipitation reaction to increase the resistance against corrosion and poisoning. …”
mentioning
confidence: 99%